Tunable electronic properties of the GeC/MoS2 heterostructures: A first-principles study. (1st April 2022) - Meng, Dongping; Li, Xiaodan; Liu, Shu; Zhang, Haoyang; Ruan, Shihao; Hu, Taotao
Abstract: First-principle calculations based on the density functional theory are carried out to investigate the structural and electronic properties of the GeC/MoS2 hetero-structures (including superlattice, hetero-bilayer and hetero-trilayer). Among all six GeC/MoS2 superlattice systems considered here, the AB stacking model (the Ge atoms are aligned on the Mo atoms, all S and C atoms are above the center of the hexagonal ring) is the most stable structure. The AB stacking GeC/MoS2 hetero-bilayer system possesses a type-II band alignment with an intrinsic direct band gap of 0.73 eV (GGA-PBE) to 1.18 eV (HSE06), which can effectively separate the photogenerated electron-hole pairs. Our results revealed that the bandgap could be modulated effectively by applying in-plane biaxial compressing/stretching (range from −3% to 3%) while maintaining the type-II band alignment. Furthermore, due to the influence of van der Waals interaction within atomic layers of heterostructures, the controllable band gaps could also be realized in trilayer MoS2 /GeC/MoS2 and GeC/MoS2 /GeC. This control over the band structure suggests the potential application of GeC/MoS2 hetero-structures to switching functions in future atomicscale electronic devices. Highlights: Structural and electrical properties of GeC/MoS2 superlattices are investigated using DFT-D3 and HSE06. The GeC/MoS2 hetero-structures are direct semiconductor with type-II band alignment. Band gaps of GeC/MoS2 hetero-bilayers could be modulated by in-plane biaxial compressing/stretching. The tunable band alignment could also be realized in trilayer systems.